2014
DOI: 10.11144/javeriana.upsy13-4.aeim
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación al español del Inventario Multidimensional de Fatiga al entorno laboral

Abstract: La necesidad de evaluar la fatiga al entorno laboral es esencial para poder desarrollar programas de prevención e intervención. El principal objetivo de este trabajo fue adaptar del inglés al español el Inventario Multidimensional de Fatiga. Se analizaron la estructura interna y la fiabilidad, y se aportaron evidencias de validez convergente. La aplicación de la escala se realizó a una muestra multiocupacional compuesta por 414 empleados. También se utilizaron varios correlatos externos y dos escalas de contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Sometimes, exploratory factor analyses are also applied (Neiva, Odelius, & Ramos, 2015;Wimalasiri, 1995), but only sample adequacy was proved in the present study, given the scale was originally validated with the same first-order trifactorial model. Previous studies have shown that content validity of a scale, in a cultural adaptation to another language, can be inferred from the analysis of the internal structure and reliability of the instrument (Boada-Grau, Merino-Tejedor, Gil-Ripoll, Segarra-Perez, & Vigil-Colet, 2014;Gouveia et al, 2015;Hutz et al, 2015). Validation of a scale based on the measure of its reliability is a widely used technique (Hutz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, exploratory factor analyses are also applied (Neiva, Odelius, & Ramos, 2015;Wimalasiri, 1995), but only sample adequacy was proved in the present study, given the scale was originally validated with the same first-order trifactorial model. Previous studies have shown that content validity of a scale, in a cultural adaptation to another language, can be inferred from the analysis of the internal structure and reliability of the instrument (Boada-Grau, Merino-Tejedor, Gil-Ripoll, Segarra-Perez, & Vigil-Colet, 2014;Gouveia et al, 2015;Hutz et al, 2015). Validation of a scale based on the measure of its reliability is a widely used technique (Hutz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%